ESTIMATION OF RIGHT VENTRICULAR DIASTOLIC FUNCTION IN PATIENTS WITH ISCHEMIC HEART DISEASE IN DIFFERENT AGE GROUPS - R. A. Gajfulin; A. N. Sumin; O. G. Arhipov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study the parameters of diastolic function of the right ventricle (RV) in patients with ischemic heart disease (IHD) in different age groups. Material and methods. Patients (n=678) with IHD aged 38 to 85 years were included into the study. They underwent echocardiography with assessment of RV diastolic function. The following parameters were assessed: rate of early and late diastolic RV filling (Et and At), rate of early and late diastolic motion of the ring of the tricuspid valve (e't and a't), the propagation velocity of RV early filling flow (Vpt). All patients were divided into 2 groups: 1st one - patients up to 60 years old (n=282) and the 2nd group - patients 60 years and older (n=396). Results. In IHD patients RV diastolic dysfunction was detected more often in older age group (34.3%) than in group of patients younger than 60 years (22.3%, p=0.008). The next findings were found in the 2nd group: increase in At; reduction in Et/At ratio and e't/a't, as well as higher levels of systolic and mean pulmonary arterial pressure and the greater the thickness of the RV wall. The following parameters of diastolic RV function correlated with age: At (p=0.004); Et/At (p=0.001); Vpt (p=0.002) and e't/a't ratio (p=0.004). Conclusion. The results should be used in assessment of diastolic RV function in patients of different age groups.